Effects of growth temperature, oxygen pressure, laser fluence and postannealing on transport properties of superconducting LaAlO3/KTaO3(111) interfaces. (2nd November 2022) - Sun, Yanqiu; Liu, Yuan; Pan, Wenze; Xie, Yanwu
Abstract: The recent discovery of superconductivity at EuO (or LaAlO3 )/KTaO3 interfaces has attracted considerable research interest. However, an extensive study on growth of these interfaces is still lacking. In this work, we have fabricated LaAlO3 /KTaO3 (111) interfaces by growing LaAlO3 thin films on KTaO3 (111) single-crystalline substrates by pulsed laser deposition. We investigated the effects of growth temperature, oxygen pressure, laser fluence, and postannealing on transport properties. We found that all these key growth parameters show important effects on transport properties, and discussed their possible mechanisms. Our present study provides useful knowledge to further optimize these interfaces.